Cognitive impairment and blood biomarkers of renal dysfunction in high-risk Nigerian population, with special attention to women and diabetes - Juan Fraile-Ramos; Faeren Dogoh; Monday Ogiator; Efosa Kenneth Oghagbon; Lydia Giménez-Llort (BMC Neurology)
Abstract Background Sub-Saharan Africans and Afro-Americans face 2-to-8 times higher risk of dementia compared to Caucasians, with Nigerian people being the highest population-at-risk. Adding to this challenge, their unique lipid profile increases their susceptibility to type 2 diabetes mellitus (DM-2), which further raises the risk of cognitive impairment (CI) by 1.5 times. Recently, we demonstrated a strong Diabetes/Dementia tandem in Nigerians, with increased cognitive vulnerability in illiterate, short-height, and diabetic Nigerian women in the eye of the storm. The combination of factors within this population makes it the optimal scenario to understand the relationship between CI and DM-2. Methods Here, we further studied the blood biochemical analysis of our Makurdi cohort and searched for correlations with standard anthropometric measures, educational level, cognitive status (as assessed with MMSE, 6-CIT) and DM-2. Results CI was prevalent across all groups, with higher incidence in DM-2 subjects and a marked sexual dimorphism. Thus, women exhibited a greater risk, especially those with low educational attainment. In the search for potential blood-based biomarkers for cognitive function, we identified those related to renal function. In particular, elevated uric acid and urea levels were associated with poorer cognitive performance, highlighting a potential kidney-brain axis connection. Conclusion Renal function blood metabolites in this Nigerian cohort have been identified as possible kidney-brain axis biomarkers of CI. Moreover, illiteracy, female sex, and DM-2 pose them a compounded risk of developing CI. These findings advocate that targeted interventions addressing educational disparities and metabolic health could be proposed to mitigate cognitive decline in these vulnerable sub-groups. The integration of these factors provides a comprehensive understanding of CI incidence in Nigeria’s population, offering new avenues for diagnosis, prevention, and treatment strategies. Clinical trial number Not applicable. Graphical Abstract